Surgical outcome after standard abdominoperineal resection: A 15-year cohort study from a single cancer centre. (December 2018) - Wilkins, S.; Yap, R.; Loon, K.; Staples, M.; Oliva, K.; Ruggiero, B.; McMurrick, P.; Carne, P.
Abstract: Background: Abdominoperineal resection (APR) is associated with a poorer oncological outcome than anterior resection. This may be due to higher rates of intra-operative perforation and circumferential resection margin involvement. The aim of this study was to audit our short and long-term results of abdominoperineal resection performed using conventional techniques and to compare this with other published series. Materials and methods: A retrospective review of all patients who had standard APR between January 2000 and December 2016 in a single institution, Cabrini Hospital, Melbourne, Australia. A total of 163 cases performed by nine different colorectal surgeons for primary rectal adenocarcinoma were identified, with their clinicopathological data analysed. Results: Using standard APR, only six patients (3.7%) were found to have a positive circumferential resection margin (CRM). There were two cases of intra-operative perforation (1.2%). Local recurrence rate was 5.6% of patients, with distant recurrence found in 24.9%. Disease-free survival at five years was 73.1%. Five-year overall survival was 66.7%, 67.9% of all deaths were cancer-related. Conclusion: Short and long-term outcomes after standard APR in this study were comparable to previous published studies. The CRM rate of 3.7% compares favourably to published positive CRM rates for standard APR which ranged from 6 to 18%. Standard APR remains a viable technique for the treatment of rectal cancer. Patient selection and adequate training remain important factors. Highlights: Retrospective study of APR for rectal cancer in a private hospital over 15 years. 163 consecutive cases of abdominoperineal resection 2000–2016. 3.7% (6 patients) had a positive circumferential resection margin. Local recurrence rate was 5.9%, disease free survival at five years 73.1%. Standard APR remains a viable technique for rectal cancer treatment.